4. Considerations on the Meaning of Sterility in the Patriarchal Cycle - Chwarts, Suzana (Circumscribere International Journal for the History of Science, 2008)
This paper focuses on the concept of sterility as idealized in the Biblical text and exemplified in the stories of Sarah and Abraham, Rebecca, Leah, Rachel and Jacob. My analysis of these stories leads to the hypothesis that sterility is one of the foundational themes of Israel's ancient past, by condensing some of the main obstacles inherent to the emergency of a people who believe to be guided by God. This new perspective on sterility was achieved by focusing on the spectrum of meanings of the Hebrew root 'qr, which includes infertility and uprooting; these, added to famine in the land, are experiences that will shape the religious conscience of Israel. This approach amplifies the perception of sterility in the Hebrew Bible, as it emerges from the text as a liminal state of deprivation , in opposition to the contents of the divine oath to the patriarchs (progeny and land). But even while enclosing lack of productivity, weakness and death, which have a negative value, Biblical sterility is not a closed circle, but a space open to potentiality, where divine revelation occurs. God reveals himself through sterility and in sterility. The originality and the notion of specificity in the biblical idea of sterility lie in this cyclical trait, which breaks the circumscription and negative orientation of sterility. The Bible presents sterility as a transitory state, an area for individual and corporate transformation of status. In an ideological system, such as ancient Israel’s, where contractual relations replace natural relations, sterility functions as a powerful symbol of the relationship among men and between men and God. And this may be the reason why sterile matriarch’s traditions were continually re-interpreted, from the 10th century BCE until the 1st century CE, and could be adapted to new contexts and make sense to distinct communities, particularly in times of crisis and transition.